MUHAMMAD HASBI ASH-SHIDDIEQY DAN PEMIKIRANNYA TENTANG HADIS - Suseno, Andi (Institut Agama Islam Syubbanul Wathon Magelang, 2024)
The development of religious activities in Indonesia cannot be separated from the development of the history of hadith studies in Indonesia. Talking about studies in Indonesia cannot be separated from the figures who are involved in it. Tengku Muhammad Hasbi Ash-Siddieqy is one of the scholars of hadith who is very qualified in his field. Not only is he active in organizations, he is also very productive in producing many works in the religious field. Hasbi's works ranging from tafsir al-Qur'an to hadith commentaries fill academic spaces that continue to be studied to this day. His expertise in the field of religious science is not only recognized nationally but also internationally. As a religious figure, it is interesting to study how Tengku Muhammad Hasbi Ash-Shiddieqy's thoughts in the field of hadith. In this paper the author tries to review how Ash-shiddieqy's thoughts in hadith studies. Some of these views are systematized by the author based on his work in the field of hadith. First, Hadith's view in his book “Sejarah dan Pengantar Ilmu Hadis”. This section discusses the nature of hadith and sunnah, the periodization of hadith, and shahaby. Second, the view of Hadith in his book “Pokok-pokok ilmu Diroyah”. It contains the criteria of hadith authenticity and fiqhul hadith. Third, the systematization of the book” Mutiara Hadis”. which contains a systematic description of the writing of the hadith commentary. Reading the biography and works of TM. Hasbi Ash-Shidqy gives the conclusion that he is an original Indonesian scholar who is very productive. The spirit of renewal that is so passionate in him makes him a cleric who is anti-fanatic in one school of thought or organization.